Digital Economic Transformation on the Impact of SMEs in Developing Countries: A Literature Review - Marhaendro Purno; Ahmad Nafis Ayyasy (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The digital economic transformation has become the main catalyst for changes in the global economic structure, particularly in developing countries. This study aims to identify and analyze the impact of the digital economy on the growth, efficiency, and competitiveness of Micro, Small, and Medium Enterprises (MSMEs). Through a literature review of various academic studies, international organization reports, and policy publications, it was found that digitalization offers significant opportunities for MSMEs in terms of broader market access, operational efficiency through automation, and improved access to digital financial services. However, various challenges also arise, such as the digital divide, limited technological literacy, and uneven infrastructure. This study concludes that the success of SME digital transformation in developing countries heavily depends on the synergy between public policy, human resource capacity building, and investment in digital infrastructure. Thus, digital economic transformation is not only an inevitability but also a strategic opportunity to promote more equitable economic inclusion.